Proceedings of the First International Conference on Advances in Computer Vision and Artificial Intelligence Technologies (ACVAIT 2022) - Ramesh Manza; Bharti Gawali; Pravin Yannawar; Filbert Juwono (Atlantis Press International BV, 2023)
This is an open access book.The first international Conference on Advances in Computer Vision and Artificial Intelligence Technologies (ACVAIT 2022) is a biennial conference organized by Department of Computer Science and Information Technology, Dr. Babasaheb Ambedkar Marathwada University, Aurangabad (MS) India, during August 1–2, 2022. ACVAIT 2022, is dedicated towards advances in the theme areas of Computer Vision, Image Processing, Pattern Recognition, Artificial Intelligence, Machine Learning, Human Computer Interactions, Biomedical Image Processing, Geospatial Technology, Hyperspectral image processing and allied technologies but not limited to. ACVAIT 2022, invites young and/or advanced researchers contributing in the theme area of the conference and also provide them platform for discussing their scientific contributions / research findings with the domain experts, exchange ideas with them and foster closer collaboration between members from the top universities / Higher Education Institutes (HEI). ACVAIT 2022, inviting domain specific work from research scholars, academician, machine learning & AI scientist, industry experts to contribute their scientific contribution in the following areas but not limited to.•Shape representation•Biometrics: face matching, iris recognition, footprint verification and many more.•Statistical, Structural and syntactic pattern recognition•Brain Computer Interface and Human Computer Interactions•Feature extraction and reduction•Biomedical Image Processing•Color and texture analysis•Speech analysis and understanding•Image segmentation•Speaker verification & Synthesis•Image compression, coding and encryption•Clustering and classification•Object recognition, scene understanding and video analytics•Machine learning algorithms•Image matching (pattern matching)•Extreme learning machine•Content based image retrieval and indexing•Artificial Intelligence Trends in Deep learning•Optical character recognition•Big data•Image & Video Forensics•Information retrieval•Pattern recognition and machine learning for Internet of Things•Data mining and Data Analytics•Pattern classification through Sensors•Pattern Recognition for Hyper Spectral Imaging•Satellite Image Processing